Altered white matter microstructure is related to cognition in adults with congenital heart disease. Issue 1 (28th December 2020) - Ehrler, Melanie; Schlosser, Ladina; Brugger, Peter; Greutmann, Matthias; Oxenius, Angela; Kottke, Raimund; O'Gorman Tuura, Ruth; Latal, Beatrice
Abstract: Adults with congenital heart disease are at risk for persisting executive function deficits, which are known to affect academic achievement and quality of life. Alterations in white -matter microstructure are associated with cognitive impairments in adolescents with congenital heart disease. This study aimed to identify microstructural alterations potentially associated with executive function deficits in adults with congenital heart disease. Diffusion tensor imaging and tract-based spatial statistics were conducted in 45 patients (18 females) and 54 healthy controls (26 females) aged 18–32 years. Fractional anisotropy of white matter diffusion was compared between groups and correlated with an executive function score, derived from an extensive neuropsychological test battery. Patients showed widespread bilateral reduction in fractional anisotropy ( P < 0.05, multiple comparison corrected) compared to controls. Lower fractional anisotropy was driven by patients with moderate and severe defect complexity (compared to controls: P < 0.001). Executive function scores were lower in patients ( P < 0.05) and associated with lower fractional anisotropy in the left superior corona radiata and the corticospinal tract (corrected P < 0.05). Our findings confirm alterations of white matter microstructure in adults with congenital heart disease, mainly in those patients of moderate to severe complexity. These alterations are associated with impairments in executive functioning. A better understanding of the neurocognitive deficits may help counselling and care of patients with congenital heart disease across their lifespan and have the potential to improve their outcome and quality of life. Abstract : As more patients with congenital heart disease are surviving into adulthood, interest mounts in the link between congenital heart disease and neurodevelopment across the lifespan. This is the first study in adults with congenital heart disease, demonstrating widespread alterations in white matter microstructure and an association with executive function deficits. Graphical Abstract: